Theology of Al-‘Ashr and Muhammadiyah Ethos: History of Thought K.H. Ahmad Dahlan - Nurazizah, Ervi; Nurhakim, Moh. (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
The aim of this research is to describe the history of K.H. Ahmad Dahlan regarding the ethos of muhammadiyah's struggle in its existence as a community organization operating in the field of ummah and its implementation in the field of religious education, so that it can be used as a guide for the successors of its struggle. This research uses a descriptive qualitative approach that is library research with a content analysis, approach where the data is obtained based on literature relevant to the theme of this research and then analyzed to obtain a conclusion. The result of this study is that the theology of Al-ashr is interpreted as the concept of modernity which becomes the foundation of Muhammadiyah's struggle in doing amar ma'ruf nahi mungkar, the mission of social justice and the community becomes the benchmark of its struggle, so that Muhammadiyah carries out movements in all fields and has a breath of renewal so that Muhammadiyah carries a mission to open progressive and open horizons of thinking.